Gambaran Kepuasan Pasien Terhadap Pelayanan Obat di Apotek Ditinjau Dari Perspektif Hukum Kesehatan - Surya Bin Mirta; Dira Oktapiani (Politeknik Negeri Jember, 2025)
Pharmaceutical services are governed by various laws and regulations that apply to pharmacy professionals and pharmacy operators. Pharmacy professionals are obligated to provide services in accordance with professional standards and applicable standard operating procedures. This study was conducted to examine patient satisfaction with pharmaceutical services at pharmacies from a health law perspective. This is a quantitative descriptive study using a cross-sectional approach. The sample for this study consisted of 303 respondents selected using accidental sampling. The instrument employed a questionnaire based on the Service Quality (SERVQUAL) model, which had been validated for both validity and reliability. Data were analyzed using the Community Satisfaction Survey (CSS). The results from the Community Satisfaction Survey revealed five components: Component 1 (reliability) with a “satisfied” rating (80.4%); Component 2 (responsiveness) with a “very satisfied” rating (82.4%); Component 3 (empathy) with a “very satisfied” rating (81.25%)—the empathy dimension; component four with the “very satisfied” category (86.4%)—the assurance dimension; and component five with the “very satisfied” category (85.3%)—the tangibility dimension. The conclusion of this study is that, based on the public satisfaction survey, the overall satisfaction with the services provided by Apotek Kombi received a conventional interval score of 83.15%, with service performance rated as “very satisfied” and service quality rated as “A” by members of the public who visited Apotek Kombi in Bandung to purchase medication.